2020
DOI: 10.3389/fimmu.2020.02071
|View full text |Cite
|
Sign up to set email alerts
|

Treatment With FoxP3+ Antigen-Experienced T Regulatory Cells Arrests Progressive Retinal Damage in a Spontaneous Model of Uveitis

Abstract: We specify the clinical features of a spontaneous experimental autoimmune uveitis (EAU) model, in which foreign hen-egg lysozyme (HEL) is expressed in the retina, controlled by the promoter for interphotoreceptor retinol binding protein (IRBP). We previously reported 100% P21 (post-partum day) IRBP:HEL single transgenic (sTg) mice, when crossed to transgenic T cell receptor mice (3A9) generating the double transgenic (dTg) genotype, develop EAU despite profound lymphopenia (thymic HEL-specific T cell deletion)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
36
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1
1

Relationship

2
4

Authors

Journals

citations
Cited by 9 publications
(38 citation statements)
references
References 59 publications
2
36
0
Order By: Relevance
“…These anergy-derived Treg suppress immunopathology and reinforce anergy induction ( 215 ). In this context, we have recently shown, in a transgenic model of spontaneous uveitis due to failure of Treg induction, that Tan convert to Treg cells as the inflammation resolves ( 119 ). Furthermore, adoptive transfer of antigen-experienced Treg completely prevented development of this spontaneous disease, showing the importance of Treg in the control of uveoretinitis.…”
Section: What Does the Gut–central Nervous System Axis Imply For Thermentioning
confidence: 99%
See 1 more Smart Citation
“…These anergy-derived Treg suppress immunopathology and reinforce anergy induction ( 215 ). In this context, we have recently shown, in a transgenic model of spontaneous uveitis due to failure of Treg induction, that Tan convert to Treg cells as the inflammation resolves ( 119 ). Furthermore, adoptive transfer of antigen-experienced Treg completely prevented development of this spontaneous disease, showing the importance of Treg in the control of uveoretinitis.…”
Section: What Does the Gut–central Nervous System Axis Imply For Thermentioning
confidence: 99%
“…Prevailing dogmata support a pathogenesis which depends on precursor frequency and antigen dosage/ availability, both of which determine whether, stochastically, such cells will become pathogenic (115)(116)(117)(118). Most recently, in a neoantigen transgenic model of spontaneous uveo-retinitis, an absolute requirement for antigen-specific T cell activation has been demonstrated while non-specifically TCR-activated T cells fail to induce disease (119). These questions have exercised researchers over many years and the concept that cross-reactive T cells, activated by a dysbiotic microbiome, might be the guilty party adds significantly to pathogenetic possibilities.…”
Section: Terminology Of Ocular Inflammation (Uveitis)mentioning
confidence: 99%
“…This qualitative and quantitative shift in bacterial colonization is associated with decreased microbial folate and SCFA production and a consequential relative increase in autoreactive immunogenic T effector cells (T eff ) [87]. T eff have been shown to traffic from the colon to target sites of autoimmunity [85,86] (e.g., intraocular tissue in the case of autoimmune uveitis), skewing the ratio of immunogenic (T eff ) to regulatory cells (T reg ) at target sites [88][89][90], ultimately breaching ocular immune privilege (IP) through unknown mechanisms, and thereby triggering autoimmune disease. Due to impaired intestinal barrier integrity in dysbiosis, pathogenic bacterial/viral/fungal/environmental antigens have facilitated access to the circulation, possibly triggering inflammation through adjuvant effects at affected sites (following antigen presentation; APC) (b).…”
Section: No Inflammationmentioning
confidence: 99%
“…In another model, in which EAU develops spontaneously due to lymphopenia and imbalance in [ T eff : T reg ] ratio, we have shown that disease can be prevented by adoptive transfer of antigen-experienced T reg , but not by naïve T reg . Furthermore, there was evidence of T an to T reg conversion [ 90 ].…”
Section: The Microbiome In Uveitismentioning
confidence: 99%
See 1 more Smart Citation